Commercializing growth : connecting valuation with management and governance methodologies - Schaufeld, Jerry ([New York City] : Apress, 2021)
Link commercial growth and value to management and governance. The guidance provided in this book helps you take the valuation of today--an arcane, statistical methodology--and bring it into the realm of modern management decision making. There is a disconnect between corporate governance/management initiatives and commercial success. Sound management and governance will help you bridge that gap between classic corporate valuation disciplines and commercial success. Project and corporate growth are both characterized by functional focus. For example, there might be a dedicated sales/marketing growth project. Metrics of success might be market share or number of units sold. In reality, growth is an overall organizational effort and must be measured by the increase in the corporate valuation. Interview data show that this is not the case and that the contributor's efforts become misaligned in the excitement and focus of the individual campaign. This book shows you how overall valuation is the true measure of success of a growth effort. It is a lesson that applies from startup to the public liquidation of the entity. What You Will Learn Allocate growth resources, including the decision process, internal governance, and empowering leadership Consider marketing and branding, such as competitive perspective, customer demographics, regulatory considerations, role of collaboration, and more Know the role of technology/IP, including the current state of application and the role of proprietary information Consider risk and downside, including company failure, loss of market share, and loss of key people/customers Who This Book Is For C-level management and above; corporate governance professionals; boards of directors; CEOs; venture and other investment organizations; business school academics, faculty, and students; and accounting, regulatory, and legal professionals.
Chapter 1: Growth an Introduction -- Chapter 2: Growth Rates -- Chapter 3: Global Perspective -- Chapter 4: Strategy and Business -- Chapter 5: Organizational Impact and Corporate Culture -- Chapter 6: Growth Resources Acquisition -- Chapter 7: Allocation of Resources -- Chapter 8: Market and Branding Considerations -- Chapter 9: Capital/ Financial Considerations -- Chapter 10: The Role of Technology -- Chapter 11: Risks and their Mitigation -- Chapter 12: Summary -- Appendix A: Before you Initiate: Investigate.
Includes bibliographical references and index.
Keywords: Economic development -- Planning; Politique économique; Economic development -- Planning; ekonomický rozvoj; ekonomická politika; Electronic books